Literary Competence and Creativity in Secondary Students - Alfonso-Benlliure, Vicente; Mínguez-López, Xavier (Revista Interuniversitaria de Formación del Profesorado. Continuación de la antigua Revista de Escuelas Normales, 2022)
Literary competence (LC) is the ability or capacity to produce and interpret literary texts. It has usually been assumed to have a close relationship with creativity, that is, the ability to find original and appropriate ideas in a specific context, although this relationship has rarely been analyzed empirically. This study tries to fill this gap by investigating the relationship between literary competence and creativity in adolescence and exploring which components of LC are especially relevant to the different criteria for creativity. A total of 193 first-year Obligatory Secondary Education (ESO) students and eight teachers of this educational level participated in the study. The students completed various LC and creativity tests, and the teachers evaluated their students’ LC according to their own professional criteria. The results show that the relationship between LC and creativity is significant, and it is especially intense in the case of literary creativity. Literary knowledge and the attitude toward literature are especially related to creativity. Among the criteria for creativity, flexibility seems to be especially sensitive to LC. No significant gender differences were found on the creativity measures, but differences were found in the teachers’ assessment of LC. Finally, the results are discussed in terms of their implications for Secondary Education.